A Patient with Recurrent Strokes: Approach to Coagulopathy - Zúñiga, Gabriel Alejandro; Kandula, Pranav; Sandefur, Hardy; Tafur, Alfonso J. (TH Open, 2023)
Despite anticoagulation recommendations, patients may present with recurrent events. While medication adherence is always a concern, assessment of anticoagulation failure demands a systematic approach, taking into account the potential limitations of anticoagulants and a review of differential diagnoses for comorbidities. We illustrate our approach in a case presentation.
Keywords: anticoagulation; venous thromboembolism; antiphospholipid antibody syndrome; recurrent strokes